2016
DOI: 10.1186/s40658-016-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

Physics of pure and non-pure positron emitters for PET: a review and a discussion

Abstract: With the increased interest in new PET tracers, gene-targeted therapy, immunoPET, and theranostics, other radioisotopes will be increasingly used in clinical PET scanners, in addition to 18F. Some of the most interesting radioisotopes with prospective use in the new fields are not pure short-range β+ emitters but can be associated with gamma emissions in coincidence with the annihilation radiation (prompt gamma), gamma-gamma cascades, intense Bremsstrahlung radiation, high-energy positrons that may escape out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
307
5
35

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(353 citation statements)
references
References 47 publications
6
307
5
35
Order By: Relevance
“…The polycarbonate was then dissolved, leaving the Zn, Cu, and Cd nanowires as shown in Figure 32. The nanowires were all irradiated by a 60 Co source, which emits at 1.17 and 1.33 MeV. All of the nanowire samples showed a strong decrease in conductivity as a function of radiation dosage, which agreed with the effects seen in the SnO2 nanowires.…”
supporting
confidence: 62%
“…The polycarbonate was then dissolved, leaving the Zn, Cu, and Cd nanowires as shown in Figure 32. The nanowires were all irradiated by a 60 Co source, which emits at 1.17 and 1.33 MeV. All of the nanowire samples showed a strong decrease in conductivity as a function of radiation dosage, which agreed with the effects seen in the SnO2 nanowires.…”
supporting
confidence: 62%
“…By contrast, radionuclides used in the studies of In-have found widespread use in nuclear medicine for SPECT imaging. Over the past decade, PET has experienced a significant increase applying a variety of positron emitting radiometals [45]. Recently, 68 Ga use in particular is showing a dramatic growth because of the applicability in labelling of diverse range of compounds and because it is obtained from a long shelf-life and relatively inexpensive 68 Ge/ 68 Ga generator system [46].…”
Section: Siderophores For Molecular Imaging Of Infectionmentioning
confidence: 99%
“…However, its 140‐keV radiation is dosimetrically less problematic than the 511‐keV annihilation photons, which are much more penetrating and cause higher dose rates. In this respect, it must be noted that the intense (>80%), high‐energy (>900 keV) gamma lines of some PET radiometals, namely 44 Sc, 89 Zr, and 86 Y, further limit their routine applicability for reasons of radiation protection (above all, due to high doses to production and nursing personnel) and may compromise image quality . Therefore, the isotope 43 Sc which lacks such gamma emission is currently brought forward as a replacement for 44 Sc.…”
Section: Prospects Of Pet Radiometalsmentioning
confidence: 99%
“…
The potential and future role of certain metal radionuclides, for example, 44 Sc, 89 Zr, 86 Y, 64 Cu, 68 Ga, 177 Lu, 225 Ac, and 213 Bi, and several terbium isotopes has been controversially discussed in the past decades. Furthermore, the possible benefits of "matched pairs" of isotopes for tandem applications of diagnostics and therapeutics (theranostics) have been emphasized, while such approaches still have not made their way into routine clinical practice.
…”
mentioning
confidence: 99%